Genetic and morphological data demonstrate hybridization and backcrossing in a pair of salamanders at the far end of the speciation continuum. (9th November 2021) - Arntzen, Jan W.; Jehle, Robert; Wielstra, Ben
Abstract: Deeply diverged yet hybridizing species provide a system to investigate the final stages of the speciation process. We study a hybridizing pair of salamander species—the morphologically and genetically drastically different newts Triturus cristatus and T . marmoratus —with a panel of 32 nuclear and mitochondrial genetic markers. Morphologically identified hybrids are mostly of the F1 generation and mothered by T . cristatus . The sex ratio of the F1 hybrid class is reciprocally skewed, with a preponderance of females in T . cristatus ‐mothered hybrids and males in T . marmoratus ‐mothered hybrids. This amounts to the Haldane effect operating in one direction of the cross. Deeper generation hybrids are occasionally produced, possibly including F1 hybrid × backcross hybrid offspring. Interspecific gene flow is low, yet skewed toward T . cristatus . This asymmetry may be caused by hybrid zone movement, with the superseding species being predisposed to introgression. The persisting gene flow between deeply differentiated species supports the notion that full genetic isolation may be selected against. Conversely, published morphological data suggest that introgressive hybridization is detrimental, with digital malformations occurring more frequently in the area of sympatry. Finally, to assist field identification, both within the area of natural range overlap and concerning anthropogenic introductions elsewhere, we document the phenotypical variation of two generations of hybrids compared with both parental species. We suggest that fluctuating range boundaries, ecological segregation, cytonuclear incompatibilities and hybrid breakdown through Bateson – Dobzhansky – Muller incompatibilities all contribute to species integrity, despite incomplete isolation during secondary contact.